Determining the harmonic components of nonlinear impedance loads in terms of resistances and reactances by using a current harmonic method. - Taci, MS; Doseyen, I (IEEE, 1998)
This paper presents the use of a current harmonic method for determining the harmonic components of nonlinear impedance loads in terms of resistance and reactance. Both the voltage and current waveforms were obtained with the aid of an a.d.c, card, and their harmonics through a harmonic analysing programme. The current and voltage harmonica were then used Co find die R and X parameters of the nonlinear element for each harmonic. Then the effective R and X values of die element were determined.
Keywords: non-linear load; harmonics; saturation; THD; power factor; Automation & Control Systems; Computer Science; Engineering; Optics; Telecommunications